Radiotherapy in practice: Physics for clinical oncology - Sibtain, Amen (Oxford University, 2014)
Trainees in oncology learn about ionising radiation, but to understand it fully they must also understand the physics relevant to its use in therapy. This is the first book written specifically for the oncology and radiation team. It begins with basic concepts and then explores the principles and practice of physics as it relates to radiotherapy, including discussion of specific types of therapy.